2012
DOI: 10.1371/journal.pone.0038636
|View full text |Cite
|
Sign up to set email alerts
|

“Even if You Know Everything You Can Forget”: Health Worker Perceptions of Mobile Phone Text-Messaging to Improve Malaria Case-Management in Kenya

Abstract: This paper presents the results of a qualitative study to investigate the perceptions and experiences of health workers involved in a a cluster-randomized controlled trial of a novel intervention to improve health worker malaria case-management in 107 government health facilities in Kenya. The intervention involved sending text-messages about paediatric outpatient malaria case-management accompanied by “motivating” quotes to health workers’ mobile phones. Ten malaria messages were developed reflecting recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Successful integration of mHealth projects into the health system requires both front-line and end-users to adopt the technology into their clinical practice and workflow, and changing clinical behaviour can be extremely difficult in any resource setting. Pilot projects are typically introduced to front-line users by in-service training, but these have been shown to be insufficient to produce clinical practice change, and any change that is produced quickly disappears unless there is adequate on-site support [34]. In fact, a systematic review showed that educational material alone has no impact on clinical behaviour [34].…”
Section: User Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful integration of mHealth projects into the health system requires both front-line and end-users to adopt the technology into their clinical practice and workflow, and changing clinical behaviour can be extremely difficult in any resource setting. Pilot projects are typically introduced to front-line users by in-service training, but these have been shown to be insufficient to produce clinical practice change, and any change that is produced quickly disappears unless there is adequate on-site support [34]. In fact, a systematic review showed that educational material alone has no impact on clinical behaviour [34].…”
Section: User Considerationsmentioning
confidence: 99%
“…Pilot projects are typically introduced to front-line users by in-service training, but these have been shown to be insufficient to produce clinical practice change, and any change that is produced quickly disappears unless there is adequate on-site support [34]. In fact, a systematic review showed that educational material alone has no impact on clinical behaviour [34]. Failure to plan for appropriate on-going on-site support will lead to failure beyond the initial pilot phase.…”
Section: User Considerationsmentioning
confidence: 99%
“…Through a public–private partnership South African HIV treatment guidelines are available through Google Play (Android devices) or the App Store (iOS devices) and preliminary data show that 6006 healthcare workers were empowered through the app and more than 200,000 people accessed the application (www.openmedicineproject.org) during its first month of implementation. The benefits of mobile technology was also demonstrated in Kenya where short reminder cell phone messages to healthcare providers maintained knowledge and enabled the implementation of guidelines more successfully, compared with once off training only (Jones et al 2012). Increased exposure to information could create new opportunities for HIV-related care to become habit/routine.…”
Section: Results: Proposed Model To Enhance Treatment Accessmentioning
confidence: 99%
“…One example of a study employing RCTs to examine the efficacy of mHealth include Watts et al, (2013) who conducted a RCT comparing the delivery modality (mobile phone/tablet or fixed computer) of a cognitive behavioural therapy intervention for the treatment of depression. Other examples based in developing countries can be found in the work of Chang et al, (2011), Hoffman et al, (2010, Jones et al,(2012), Lester et al,(2010); Mbuagbaw et al,(2012), Pop-Eleches et al, (2011), & Zurovac et al, (2011. …”
Section: Factorialmentioning
confidence: 99%